A Curious Case Report of “Nosey” Calcification - S Padmavathi; G Anuradha; A Kannan; C L Krithika (Journal of Indian Academy of Oral Medicine and Radiology)
Ectopic mineralization, or pathologic calcifications, occur outside the skeletal system. While rare in adults, nasal foreign bodies are common in children and mentally disabled patients. Often asymptomatic, they can remain unnoticed for years. This article presents an unusual case of a nasal foreign body in a 46-year-old male, incidentally discovered during routine dental radiography. The patient complained of tooth pain and sensitivity, with a history of sinusitis and hypertension. Radiographic examination revealed a radiopaque lesion in the right nasal cavity, causing deviation of the nasal septum. A clinical diagnosis of a foreign body was made, considering differential diagnoses such as rhinolith or parasitic infection. This case underscores the importance of thorough examination and attention to detail by dentists. Improved communication and careful radiograph interpretation can lead to the discovery of unexpected findings, facilitating accurate diagnosis and treatment.